Effectiveness of a starch thickened infant formula with reduced lactose content, probiotics and prebiotics on quality of life and clinical outcome in infants with regurgitation and/or colic - Chouraqui, Jean-Pierre; Brancato, Sandra; Delmas, Berenice; Hanh, Thierry (Frontiers in Nutrition, 2023)
Background Regurgitation and colic are quite common in young infants, leading to a reduced quality of life (QoL) and to parental distress. Their management is challenging and aims to effectively reassure and relieve symptoms. This study aimed to assess the effectiveness over 30 days of a starch thickened formula with a reduced lactose content, Limosilactobacillus reuteri (Lactobacillus reuteri) DSM 17938 and FOS/GOS. Methods A real-world prospective multicenter experimental study was conducted in a before-after design within subject. Full term infants 0−5 months with regurgitation or colic or both symptoms and without intercurrent illness were included after parental informed consent and received the studied formula. The primary endpoint was the improvement in QoL using the QUALIN infant’s questionnaire. Secondary endpoints were the symptoms outcome and the formula tolerance. Results Of the 101 infants included (age: 6.2 ± 4.3 weeks), 33 had regurgitation, 34 colic and 34 had both. At D30, the QoL score was improved in 75% of infants in per protocol analysis (n = 68; +8.2 ± 13.7; p < 0.001), more in those with colic or both symptoms. Meanwhile, in intention to treat analysis (all p < 0.001), the daily number of regurgitations decreased by 61% and the weekly number of days with colic by 63% while the daily cumulative duration of crying decreased by 82 ± 106 mn. These improvements were observed within the first week by 89 and 76% of parents, respectively. Conclusion The study formula associated with reassurance is shown to be quickly effective in the management of infant’s regurgitation or/and colic in routine clinical practice. Clinical trial registration https://clinicaltrials.gov/, identifier NCT04462640.